PENGAMATAN TERHADAP PERILAKU SISWA KELAS IV SDN PANGULAH UTARA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Yasintha Diva Anjani; Zahra Aida Kamila; Ady Prasetyo Ryan Nugroho; Ilham Muhamad Yasin; Siti Khulasoh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is part of the implementation of the assignment in the Classroom Action Research (CAR) course implemented in class IV of SDN Pangulah Utara. The purpose of this study was to describe the condition of students during Islamic Religious Education (PAI) learning, especially in terms of learning concentration, writing skills, and responses to the learning methods used. In this activity, the researcher also acted as a substitute teacher for one meeting. Based on the results of the observation, it was found that most students, especially boys, had difficulty in maintaining learning focus, tended to joke a lot, and created a noisy atmosphere. There were four students who were not yet able to write, while some others showed untidy writing. Ice breaking in the form of songs was sung to attract students' attention, but it did not provide optimal results. The learning was closed with the activity of reading short letters together, starting from the letter An-Naas to At-Takatsur.